Software visual specification for requirement engineering education - Fauziah, Zainuddin; Ruzaini, Abdullah Arshah; Rozlina, Mohamed (ACM, 2019)
Requirement engineering course is perceived as an important course that become one of compulsory courses to be thought to Software Engineering graduates. However, Requirement Engineering Education (REE) is suffering from difficulty in content delivery (lecturer) and learning (student) due to the nature of Requirement Engineering theoretical and diversity of knowledge. In order to overcome this problem, software visualization approach is introduced in learning requirement engineering course. A control experiment was conducted to identify the effectiveness of the approach. Based on the analysis of the survey data, the proposed approach seems able to give positive impact to the quality of overall requirement specification.